Managing extensive mitral valve and ventricular septal injuries secondary to penetrating trauma. (7th September 2017) - Han, Frank Y; Reyes, Karl G; Bleiweis, Mark S
Abstract: Penetrating cardiac injuries with extensive intracardiac components and minimal epicardial components are a rare presentation. A 31-year-old male presented with complex mitral valve and ventricular septal injuries with partial atrioventricular disruption but with hardly visible epicardial injuries; the patient's presentation, progression of injuries and successful management are discussed.